Conservation tillage and diversified cropping enhance system productivity and eco-efficiency and reduce greenhouse gas intensity in organic farming - Babu, Subhash; Singh, Raghavendra; Avasthe, Ravikant; Rathore, Sanjay Singh; Kumar, Sanjeev; Das, Anup; Layek, Jayanta; Sharma, Vikas; Wani, Owais Ali; Singh, Vinod Kumar (Frontiers in Sustainable Food Systems, 2023)
Environmental pollution, resource dwindling, and soil degradation questioned the sustainability of contemporary agricultural production systems. Organic farming is advocated as a sustainable solution for ensuring food security without compromising environmental sustainability. However, poor farm productivity quizzed the sustainability of organic production systems. Hence, a field study was carried out in the Sikkim region of the Indian Himalayas to assess the efficacy of conservation-effective tilling and diversified cropping on system productivity, profitability, environmental quality, and soil nutrient balance in organic farming. Three tillage systems, namely, (i) conventional tillage (CT), (ii) reduced tillage (RT), and (iii) zero tillage (ZT), and four maize based diversified cropping systems (maize–black gram–toria, maize–black gram–buckwheat, maize–rajmash–toria, and maize–rajmash–buckwheat) were tested using a three times replicated split-plot design. The ZT system recorded 13.5 and 3.5% higher system productivity over CT and RT, respectively. Of the four diversified cropping systems, the maize–rajmash–buckwheat system recorded the maximum system productivity (13.99 Mg ha−1) and net returns (3,141 US ha−1) followed by the maize–black gram–buckwheat system. Among the tillage practices, ZT recorded the significantly high eco-efficiency index (EEI; 1.55 US per kg CO2-eq emission) and the lowest greenhouse gas intensity (GHGI; 0.15 kg CO2-eq per kg production). Of the diversified cropping systems, the maize-rajmash-buckwheat registered the lowest GHGI (0.14 CO2-eq per kg production) and the highest EEI (1.47 US per kg CO2-eq emission). Concerning soil nutrient balance, after three cropping cycles, the soil under ZT recorded significantly higher available N (340.0 kg ha−1), P (16.6 kg ha−1), and K (337.3 kg ha−1) over the CT system at 0–10 cm soil depth. Similarly, the soil under the maize–black gram–buckwheat system had the maximum bio-available NPK. Thus, the study suggests that the cultivation of the maize–black gram/rajmash–buckwheat systems under ZT and/or RT would increase farm productivity, profitability, and soil fertility with minimum GHGI in organic farming under the Eastern Himalayan region of India.